2019
DOI: 10.1152/ajpregu.00083.2019
|View full text |Cite
|
Sign up to set email alerts
|

Early hyperbaric oxygen therapy improves survival in a model of severe sepsis

Abstract: Sepsis is a major clinical challenge, with therapy limited to supportive interventions. Therefore, the search for novel remedial approaches is of great importance. We addressed whether hyperbaric oxygen therapy (HBOT) could improve the outcome of sepsis using an acute experimental mouse model. Sepsis was induced in male CD-1 mice by cecal ligation and puncture (CLP) tailored to result in 80–90% mortality within 72 h of the insult. After CLP, mice were randomized into two groups receiving HBOT or not at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
(62 reference statements)
4
30
0
Order By: Relevance
“…A recent study showed that the bacterial load within the peritoneal fluid and blood was not affected by HBOT in the CLP sepsis model. The authors concluded that, in that polymicrobial sepsis model, HBOT did not have a direct bactericidal effect [ 32 ]. However, our study results may not be affected by the presence or absence of a direct, HBOT-mediated bactericidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the bacterial load within the peritoneal fluid and blood was not affected by HBOT in the CLP sepsis model. The authors concluded that, in that polymicrobial sepsis model, HBOT did not have a direct bactericidal effect [ 32 ]. However, our study results may not be affected by the presence or absence of a direct, HBOT-mediated bactericidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of drug treatments to limit lethality and vaccines to curve down COVID-19 infections have left clinicians with the single option of using supportive therapy as the only intervention, such as the delivery of oxygen and fluids, and mechanical ventilation as the last resource. Experimental animal studies about the response to sepsis have suggested that early interventions are critical to ameliorate the condition, such as source control of the infection or injury (Cauvi et al 2012;Cauvi et al 2019), the use of antibiotics (Puskarich et al 2009), or a reduction in the inflammatory response (Halbach et al 2019). Indeed, the Surviving Sepsis Campaign calls for early administration of supportive therapy (e.g., antibiotics and fluids) to ameliorate the disease (http://www.…”
mentioning
confidence: 99%
“…In this regard, hyperbaric oxygen therapy (HBOT) that consists of exposure to 100% oxygen under increased atmospheric pressure up to 2.4 atm could be a great resource to improve the outcome from the infection when it is administered at early stages as soon as a reduction of arterial oxygen concentration is detected. Indeed, experimental animal studies have shown that an initial HBOT improved dramatically the outcome from sepsis, which was correlated with a reduction of the inflammatory response triggered by the initial insult (Halbach et al 2019). The great advantage of HBOT is that it delivers oxygen at elevated partial pressure allowing this gas to penetrate tissues very rapidly and in higher concentration, which is more effective than hemoglobin oxygen delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HBOT can directly reverse tissue hypoxia and is anti-inflammatory-both global pathologic features of COVID-19 disease. Most recently, HBOT reduced hepatic cytokine production in a rodent model of severe, polymicrobial sepsis (Halbach et al 2019). HBOT has been shown to reduce circulating cytokine levels in individuals with Crohn's disease (Weisz et al 1997).…”
mentioning
confidence: 99%